The disulfide catalyst QSOX1 maintains the colon mucosal barrier by regulating Golgi glycosyltransferases. (17th October 2022) - Ilani, Tal; Reznik, Nava; Yeshaya, Noa; Feldman, Tal; Vilela, Patrick; Lansky, Zipora; Javitt, Gabriel; Shemesh, Michal; Brenner, Ori; Elkis, Yoav; Varsano, Neta; Jaramillo, Ana M; et al.
Abstract: Mucus is made of enormous mucin glycoproteins that polymerize by disulfide crosslinking in the Golgi apparatus. QSOX1 is a catalyst of disulfide bond formation localized to the Golgi. Both QSOX1 and mucins are highly expressed in goblet cells of mucosal tissues, leading to the hypothesis that QSOX1 catalyzes disulfide‐mediated mucin polymerization. We found that knockout mice lacking QSOX1 had impaired mucus barrier function due to production of defective mucus. However, an investigation on the molecular level revealed normal disulfide‐mediated polymerization of mucins and related glycoproteins. Instead, we detected a drastic decrease in sialic acid in the gut mucus glycome of the QSOX1 knockout mice, leading to the discovery that QSOX1 forms regulatory disulfides in Golgi glycosyltransferases. Sialylation defects in the colon are known to cause colitis in humans. Here we show that QSOX1 redox control of sialylation is essential for maintaining mucosal function. Synopsis: The enzyme QSOX1 introduces activating disulfide bonds into sialyltransferases in the Golgi apparatus of intestinal goblet cells, promoting incorporation of sialic acid into glycans and construction of protective colon mucus. Golgi redox regulation maintains a resilient colon mucosal barrier. Knockout of QSOX1 alters colon glycome, microbiome, and sensitivity to colitis. QSOX1 introduces regulatory disulfide bonds into Golgi glycosyltransferases. QSOX1 is not required for disulfide-mediated polymerization of mucins. Abstract : The Golgi‐localized enzyme QSOX1 is required for the establishment of a protective mucus layer by promoting sialic acid incorporation into mucosal glycans.